Translational and pharmacokinetic‐pharmacodynamic application for the clinical development of GDC‐0334, a novel TRPA1 inhibitor. Issue 5 (31st May 2021) - Chan, Phyllis; Ding, Han Ting; Liederer, Bianca M.; Mao, Jialin; Belloni, Paula; Chen, Liuxi; Gao, Simon S.; Joseph, Victory; Yang, Xiaoying; Lin, Joseph S.; Mitra, Mayur S.; Putnam, Wendy S.; et al.
Abstract: GDC‐0334 is a novel small molecule inhibitor of transient receptor potential cation channel member A1 (TRPA1), a promising therapeutic target for many nervous system and respiratory diseases. The pharmacokinetic (PK) profile and pharmacodynamic (PD) effects of GDC‐0334 were evaluated in this first‐in‐human (FIH) study. A starting single dose of 25 mg was selected based on integrated preclinical PK, PD, and toxicology data following oral administration of GDC‐0334 in guinea pigs, rats, dogs, and monkeys. Human PK and PK‐PD of GDC‐0334 were characterized after single and multiple oral dosing using a population modeling approach. The ability of GDC‐0334 to inhibit dermal blood flow (DBF) induced by topical administration of allyl isothiocyanate (AITC) was evaluated as a target‐engagement biomarker. Quantitative models were developed iteratively to refine the parameter estimates of the dose‐concentration‐effect relationships through stepwise estimation and extrapolation. Human PK analyses revealed that bioavailability, absorption rate constant, and lag time increase when GDC‐0334 was administered with food. The inhibitory effect of GDC‐0334 on the AITC‐induced DBF biomarker exhibited a clear sigmoid‐Emax relationship with GDC‐0334 plasma concentrations in humans. This study leveraged emerging preclinical and clinical data to enable iterative refinement of GDC‐0334 mathematical models throughout the FIH study for dose selection in subsequent cohorts throughout the study. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? GDC‐0334 is a novel, small molecule TRPA1 inhibitor and a pharmacokinetic‐pharmacodynamic (PK‐PD) modeling strategy could be implemented in a systematic and step‐wise manner to build and learn from emerging data for early clinical development. WHAT QUESTION DID THIS STUDY ADDRESS? Can noncompartmental and population‐based analyses be used to describe the PK and PD characteristics of GDC‐0334 in preclinical and clinical studies? WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? GDC‐0334 exposure generally increased with dose in rats, dogs, and monkeys. The starting dose (25 mg) in the clinical study was determined based on the preclinical data. GDC‐0334 exhibited linear PK in humans and the bioavailability was increased with food. The inhibitory effect of GDC‐0334 on dermal blood flow induced by the TRPA1 agonist allyl isothiocyanate in humans indicates a clear PK‐PD relationship. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? The models developed based on TRPA1 agonist‐induced dermal blood flow inhibition data can be used to predict PK‐PD relationships in future preclinical and clinical studies evaluating new drug entities that target TRPA1.